Modernitas dan Tragedi: Kritik dalam Sosiologi Humanistis Zygmunt Bauman - Robet, Robertus (Masyarakat: Jurnal Sosiologi, 2015)
There are only two different occurances in modernity: solid modernity and liquid modernity. Solid Modernity operates to create logic of order, categorization and administration. Liquid Modernity works as an illusion of speed and perpetual changes. Mode of categorization in solid modernity has sparked the logic of partiality and nonpartialitity in society. Holocaust -according to Bauman- is an impact of the incapability of the modernity to define ambivalence subject in the mode of categorization. Jews is historical subject that is ambivalence in the eye of regime of categorization. Based on this historical trauma, Bauman propose a new horison in Sociology: Sociology that gives more commitment to truth and ethics.